ANALISIS IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM MENINGKATKAN AKTIVITAS BELAJAR SISWA PADA MATA PELAJARAN IPS SMP NEGERI 8 PEKANBARU - Damayanti, Novi; Sumarno, Sumarno; Suarman, Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to know the implementation of the scientific approach in improving students learning activities, and students' perceptions of the application of the scientific approach in learning process. This research was conducted at Junior high school 8 pekanbaru on March - December 2019 with research respondents of all of students from VIII2, VIII6, VIII10, and 3 teachers. The data collected through observation, and questionnaire. Observations were made to collect data on activities undertaken by teachers and learning activities undertaken by students, distribution of questionnaires to students to collect data on students' perceptions about the application of scientific approaches in social studies learning Based on the results of data analysis, it can be concluded that 1) The application of the scientific approach to social studies subjects has been well implemented. 2) students' perceptions of the application of the scientific approach to social studies subjects is included good categories. Thus the use of the scientific approach by teachers, especially in social studies subject in addition to increase student learning activities are also appropriate with the expectations and desires of students.Key Words: Implementation of Scientific Approaches, Students’ Learning Activities, Students’ Perceptions.